Prediction of Solar Radiation using Empirical Models over Lowland Region Nepal - Pokhrel, A. K.; Adhikari, H. P.; Joshi, U.; Tiwari, B. R.; KC, B. R.; Poudyal, K. N. (Journal of Nepal Physical Society, 2023)
Renewable energy sources are becoming more and more popular as a result of the world’s rapidly rising energy needs and the depletion of fossil fuel stocks. Solar energy significantly increases the need for electricity. Due to high energy demands, solar energy most viable out among all of energy sources. Before choosing a location for a solar-powered power plant, it is necessary to predict or anticipate solar energy. For the estimation of the solar energy we use meteorological parameters such as sunshine hour, temperature and relative humidity on selected empirical models to find the empirical coefficients at the study site Biratnagar (Lat. 26° 27’ 15" E, Long. 87° 16’ 47" N, and alt. 72 m) Nepal. Regression technique is utilized on meteorological parameters including global solar radiation at different models viz. Angstrom-Prescott (A-P) model, Ogunlade model, Gopinathan model and Hargreaves model. Among the four models, the A-P model is better than other models by analyzing the statistical tools. Finally, the empirical constants of A-P model and are found. The finding coefficients can be used to estimate the solar radiation and solar energy at similar geographical locations of Nepal.